Dynamics of leaf area formation in corn hybrids of different maturity groups depending on foliar fertilization (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2025)
The results of two years of research on the effect of foliar fertilization on the dynamics of leaf area formation in corn hybrids of different maturity groups: P 7818, DKS 3730, and DKS 4541 are presented.Formulation of the problem. Research into the possibility of regulating the formation of the leaf surface of corn crops through foliar feeding will significantly improve the accumulation of plastic substances in the process of photosynthetic activity of crops. That is why research in this area is relevant and timely.The aim of the research was to determine the effect of foliar feeding with products of different bases on the dynamics of leaf area formation and the size of the rolled leaf of corn hybrids of different maturity groups.Research methods. A two-factor field experiment was set up using the split-plot method in four replicates. The first-order plots (factor A) consisted of three modern corn hybrids of different maturity groups: early-maturing P 7818 (FAO 240); medium-early DKS 3730 (FAO 280) and medium-maturing DKS 4541 (FAO 380).The second-order plots were seven variants of foliar feeding with various combinations of water-soluble fertilizers and stimulants-antistressants: I – control (spraying of experimental plots with water); II – foliar feeding with a mixture of urea (N10) and Nanovit complex fertilizer (1.5 l/ha) in the 14-16 microphase; III – foliar feeding with a mixture of urea (N10) and Nanovit complex fertilizer (1.5 l/ha) in the 16-18th microphase; IV – II + III; V – foliar feeding with a mixture of urea (N10) and Nanovit complex fertilizer (1.5 l/ha) and Quantum AminoMax anti-stress agent (1.0 l/ha) during the 14-16th and 16-18th microphases; VI – V + addition to the tank solution during the first feeding of zinc fertilizer Partner (1.0 l/ha); VII – V + addition to the tank solution during the first and second feeding of zinc fertilizer Partner (1.0 l/ha). The area of the sowing plot was 140 m2, and the accounting area was 100 m2.Research results. It has been established that both the maturity group of hybrids and foliar fertilization affect the leaf area of corn crops. Among the hybrids studied, the medium-maturing hybrid DKS 454 formed the largest leaf area in all phases of the study. In particular, during the 33rd, 65th, 75th, and 85th microphases according to the BBCH classification, the leaf area of this hybrid averaged 25.9 thousand m2/ha, 37.6, 35.1, and 31.6 thousand m2/ha, respectively, over the years.All studied variants of two foliar feedings ensured the formation of a significantly higher leaf surface area of all corn hybrids during the 33rd, 65th, 75th, and 85th micro-phases, with the largest area observed in the variants of two foliar feedings during the 14-16th and 16-18th microphases with a mixture of urea at a dose of 21 kg/ha, Nanovit complex fertilizer at a dose of 1.5 l/ha, and Quantum AminoMax stimulant-antistressant at a dose of 1.0 l/ha. The increase in leaf area of the studied corn hybrids in all phases of the study compared to the control was 12–15%. The addition of Partner zinc fertilizer to this solution did not provide a further increase in leaf area for any of the studied hybrids.The area of the attached leaf of all corn hybrids was largest in the variants of foliar feeding with a combination of all products (urea, Nanovit, Quantum AminoMax, Partner), while it did not differ significantly from the variant where a solution of three products was applied (without the addition of Partner zinc fertilizer). In these variants, the area of the attached leaf of corn hybrids P 7818, DKS 3730, and DKS 4541 averaged 420.7-421.6 cm2, 541.6-545.6 cm2, and 547.0-550.1 cm2, respectively, over two years of research.Conclusions. Therefore, in order to form a larger leaf surface area of crops, which creates more favorable conditions for the formation of higher corn grain yields of different maturity groups, it is advisable to carry out two foliar feedings during the 14-16 and 16-18 microphases according to the international BBCH classification with a solution of urea at a dose of N10, complex water-soluble fertilizer Nanovit at a dose of 1.5 l/ha, and stimulator-antistressant Quantum AminoMax 200 at a dose of 1.0 l/ha.
Keywords: corn; hybrid; growth stimulants; water-soluble fertilizers; anti-stress agent; foliar feeding; leaf area